Fluid substitution in porous rocks with aligned cracks: Theory versus numerical modeling - Brown, L.; Gurevich, Boris; Makarynska, D.; Arns, C.; Knackstedt, M. (2006)
The effect of penny-shaped cracks on the elastic properties of porous media is modeled using static finite element modeling (FEM) code. Anisotropic Gassmann theory is used to predict the effective properties of the saturated cracked media from their dry properties. There is an excellent agreement between numerical results and theory, with a small error associated with partially inequilibrated patches of fluid in the FEM. These patches of fluid result in a residual stiffness which can be subtracted from the FEM results to further improve agreement with Gassmann theory.